Interpretasi Perjanjian Internasional Terkait Historical Rights Dalam UNCLOS 1982: (Studi Kasus: Sengketa Laut Cina Selatan antara Republik Rakyat Cina v. Filipina dan Sengketa Kepulauan Chagos antara Mauritius v. Britania Raya) - Ninne Zahara Silviani (Program Studi Ilmu Hukum Universitas Maritim Raja Ali Haji, 2019)
People’s Republic of China with 9-dash-lines designed in 1947, claimed almost 90% of the South China Sea’s Area. Generally known the line not only overlapping in one Asean Country but five other countries which, The Philippines, Indonesia, Malaysia, Vietnam and Brunei Darussalam. The Philippines took its fight over its territory to the Permanent Court of Arbitration, Den Haag in 2013. In 12th July 2016, Permanent Court of Arbitration Award declared that China has no legal basis for claiming territorial waters in the South China Sea. Yet, the PRC does not accepted the Award. PRC denied the decision due to the PRC’s interpretation to UNCLOS 1982 regulation and declared their sovereignty across the archipelagic islands in South China Sea by historical reasons. A Similar disputes was happen between Mauritius v. United Kingdom in 2010-2015 due to the Maritime Protected Area in Chagos Islands on Indian Ocean whose claimed by Mauritius because of historical reasons. This article will examine how VCLT 1969 reacted to the violation of UNCLOS 1982 which known as a package deal in accordance to regulate the sovereignty of water territory. This article is a normative legal research with secondary data, which obtained from library study descriptively.